405 PLASMA LEVELS OF C-REACTIVE PROTEIN IN OVERWEIGHT CHILDREN AND ADOLESCENTS WITH CARDIAC-RELATED FAMILIAL RISK FACTORS. (1st January 2006) - Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Cass, K. A.; Kip, K. T.; Rothman, A.; Luna, C. F.; Gustafson, A.; Lowe, A.; Coviello, L.; Restrepo, H.
Abstract : Background: Obesity has been associated with elevated C-reactive protein and increased cardiovascular risk. Genetic predisposition to atherosclerosis constitutes important risk for developing coronary artery disease (CAD). Objectives: To assess the relationship of some cardiac-related familial risk factors (FRF) with the plasma level of highly sensitive C-reactive protein (hs-CRP) in a group of overweight children and adolescents. Methods: This study included 101 children and adolescents with body mass index (BMI) ≥ 95th percentile, whose parents answered a questionnaire to address the familial history of diabetes, hypercholesterolemia, hypertension, heart attack, and congenital and/or acquired cardiac diseases. All children participated in a 12-week medically supervised risk factor reduction program. Fasting blood samples were drawn for determination of hs-CRP during the first visit. Results: There were 54 males and 47 females, mean age: 11.3 years (range: 5-17), mean BMI Z-score: 2.37 ± 0.32, Hispanic: 50%, Caucasian: 30%, African American: 17%, other races: 3%. There were 36 patients with 1 or none FRF and 65 with 2 or more FRF. Conclusion: In this group of overweight children and adolescents the presence of 2 or more familial cardiac-related risk factor was significantly associated with elevated plasma levels of hs-CRP. Elevation of hs-CRP in obese children and adolescents may help identify those individuals at high risk to develop CAD later in life.